Suddenly engaged - London, Julia (London, Julia. Lake Haven novel., 2017)
Single mother Kyra Kokinos spends her days waiting tables, her nights working on her real estate license, and every spare moment with her precocious six-year-old daughter, Ruby - especially when Ruby won't stop pestering their grumpy next-door neighbor. At first glance, Dax Bishop seems like the kind of gruff, solitary guy who'd be unlikely to offer a cup of sugar, let alone a marriage proposal. But that's exactly what happens when Ruby needs life-saving surgery. Dax showed up in East Beach a year ago, fresh from a painful divorce and looking for a place where he could make furniture and avoid people. Suddenly his life is invaded by an inquisitive munchkin in sparkly cowboy boots - and her frazzled, too-tempting mother. So he presents a practical plan: his insurance will help Ruby, and then they can divorce - zero strings attached. But soon Kyra and Dax find their engagement of convenience is simple in name only. As their attraction deepens, a figure from the past reappears, offering a way out. Can Kyra and Dax let go so easily - or has love become a preexisting condition?